Effectiveness of Planned Teaching Program on Self-care for Patients with Diabetes Mellitus in a Selected Community at Tumkur - Shaikh, Rijvana Javed; Shaikh, Heena Kadar (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: The aim of this study is to find the Effectiveness of planned teaching program (PTP) on self-care for patients with diabetes mellitus in a selected community at Tumkur. Materials and Methods: The investigation was quantitative. This study used a non-equivalent control group quasi-experimental design. The study took place at Kaivara. This study includes all Kaivara diabetics. Data were collected from 30 diabetics. This study used purposive sampling methods. Data analysis makes use of both inferential (paired and unpaired “t” tests) and descriptive (mean, standard deviation, frequency, and percentage) statistics. Result: Group I patients had pre- and post-test knowledge scores of 18–60 and 84–101. For Group I, the mean knowledge score after the test (93.67) was higher than the mean score before the test (33.8). The “t” value for Group I (“t” = 22.10) demonstrated a notable change, demonstrating PTP increased diabetic patients’ understanding. Group I patients’ self-care practice scores also changed significantly. Group I patients’ pre-test and post-test self-care practice scores were 22–56 and 63–75. Mean post-test score for self-care (70.53) was greater than pre-test. The Group I “t” value (16.19) demonstrated a significant difference, demonstrating that PTP increases diabetes mellitus patients’ self-care practices. The mean post-test knowledge score on frequent check-ups, exercise, and food (97, 98.92, and 98.38) was significantly greater than the score on the pre-test following PTP. The mean percentage of self-care practice score for medications (96.67) and skin care (99.13) increased significantly for Group I. Conclusion: The experimental and control groups had substantial differences in post-test self-care and knowledge scores, proving that individual-planned teaching program work.